A ten-year experience of physical Intimate partner violence (IPV) in a French forensic unit. (February 2017) - Savall, Frédéric; Lechevalier, Agathe; Hérin, Fabrice; Vergnault, Marion; Telmon, Norbert; Bartoli, Christophe
Abstract: Forensic units have a central role to play in healthy public policy, by the collection and management of violence. This study aims to describe the characteristics of physical Intimate Partner Violence (IPV) against men reported over 10 years in the forensic unit of Toulouse (France) and to compare them with the characteristics of physical IPV against women over the same period. All the medico-legal reports of male victims over 18 years of age between 2005 and 2014 were analyzed. Female victims over 18 years of age in the same period were randomized by year in order to study a similar number of individuals. We analyzed 712 forensic reports of male victims and 865 forensic reports of female victims. Repeated consultation concerned 20.5% of women and 7.5% of men (p < 0.001). More male victims than female victims consulted in an emergency unit (p < 0.001). The most frequently alleged manner of attack was punching for male victims (34.1%) and grabbing or pushing for female victims (86.7%). There were fewer wounds and vascular or visceral injuries for female victims (p = 0.001). There were more reports of no injury for female victims (p < 0.001) and fewer reports with at least two injuries (p = 0.002). The most common injuries were superficial skin injuries (abrasion, bruise or hematoma) for both groups. On the one hand, physical IPV against women was more frequent than against men, while physical IPV against men seemed to be more severe than against women. The distribution of alleged manners of attack and injuries were consistent with previous studies. However, the mechanisms of the origin of the process of violence are difficult to apprehend in such a dyadic context. The findings should be interpreted with caution, but they provide original and substantial material, which can be useful in recognizing victims and in developing preventive strategies. With this aim, forensic units have a central role to play in the collection of violence and in individualized management. In France, this subject has not been extensively studied and future research is needed to emphasize the characteristics of IPV in order to better understand the phenomenon and to create and assess public policies in order to prevent it. Highlights: We described the characteristics of physical Intimate Partner Violence (IPV). We compared physical IPV against men and against women. Women are more exposed to physical IPV than men. Physical IPV against men is not infrequent and could be severe. This kind of data is essential to improve screening and management of violence.